Módulo medico multi-operacional transportable para emergencias - Diaz Vega, Jedy Katerin (Universidad Antonio Nariño, 2021)
The world is changing and as shown we have climatic changes that are usually abrupt and cause great damage to those who inhabit it, but the question is based on the fact that the greatest cause of this purpose is the human being and in this way is the greatest affected. Therefore, an architectural idea is exposed in order to attribute an object to the emergency that can provide users with health care, a Multi-functional equipment that adapts to the terrain and that manages to provide priority medical care. As problematic we have the lack of information we have about emergency modules, regu-lations and operating guidelines, such as tell us that the initial prototype is the first in opera-tion for this type of natural emergency. Contemplating these aspects, the Multi-functional module provides security for people who provide the service and people who need help in their emotional and physical state, without a doubt this module is designed for this type of care, but its functionality is open to providing health days remote and hard to reach places. This architectural module handles an assembly articulation concept where the greater the im-pact of the emergency, the module adapts to this problem. Its concept is geometric and there-fore constructible, its assembly process is fast and efficient, its initial prototype is the basis for the development of a larger attention complex, that is if we acquire prototype 1 we can inte-grate 2 or 6 prototypes to this and will be able to be a unified whole.